Peptides for In Vivo Target-Specific Cancer Imaging - Ferro-Flores, G.; de M. Ramirez, F.; Melendez-Alafort, L.; Santos-Cuevas, C. L. (Mini Reviews in Medicinal Chemistry, 2010)
Molecular imaging comprises non-invasive monitoring of functional and spatiotemporal processes at molecular and cellular levels in living systems. Advanced imaging techniques can monitor such processes. Peptide receptors over-expressed in tumours can be targeted by peptides conjugated to radionuclides, near-infrared fluorochromes, metallic nanoparticles or quantum dots for target-specific cancer imaging.
Keywords: Peptides